Важливість подвійного оподаткування для збільшення експортного потенціалу Грузії - Baratashvili, Nazi; Pharsenadze, Zaza (Dr. Viktor Koval, 2018)
Introduction. According for future economic development of country and creation strong stable political framework is essential to improve international existing mechanism of avoiding double taxation. Double taxation avoidance system is an essential component of good business environment and is a key factor of stimulating investments. Agreements of Double taxation provide legal framework of releasing from double taxation. In spite of that, such exemption is foreseen by the internal law of different countries, international double taxation agreements provides contingency approach. Aim and tasks. The aim of the article is to study the directions of avoiding double taxation, which contributes to the deepening of economic cooperation between countries and attracting investment. The task is to study and show the positive and negative sides of double tax treaties. Results. One of the main factor of countries economic development is to promote export. For that every country is interested in incensement of export share per capital in foreign trade. In the article is analysed trends of development of international double taxation principles and forms. Research shows and confirms that an effective legal mechanism in Georgia is still in the process of formation in this field. Trade liberalization contributes to the creation of such flexible mechanisms, which allow developing countries receive maximal benefits from the process of world economic development. Also, Georgia received economic benefits from agreement of Avoidance of Double Taxation, which was signed all parties. Conclusions. We have to mention that for Georgia is great challenge to increase export share per capital in European Union countries. Georgian has real ability to increase export potential in EU countries. The result of this is deep and comprehensive Free Trade Agreement (DCFTA) with the European Union and agreement of Avoidance of Double Taxation and the Prevention of Fiscal evasion (DTAA) with respect to taxes on income. It promotes to build further new trade economic cooperation between countries by safeguarding the interests of involved countries according the agreement.